Book review: Globalisation and post-tourism: local off-shoots of new global and virtual habits - Joan Jurado Rota (Revista CIDOB d'Afers Internacionals, 2016)
Review of the book: Russo, Antonio Paolo y Richards, Greg (eds.) Reinventing the Local in Tourism Channel View Publications, 2016. 288 págs.